2019
DOI: 10.1038/s41366-019-0423-z
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis on the relationship between prenatal stress and metabolic syndrome intermediate phenotypes

Abstract: Background Metabolic Syndrome (MetS) can be considered as a consequence of a complex interplay between genetic and environmental factors and can be influenced by changes in the environment early in life. Prenatal stress (PS) exposure likely represents an important adverse intrauterine environment that may impact the biology of the developing organism. The aim of this study was to quantitatively synthesize the available data on the effects of PS on offspring's obesity, estimated indirectly by body mass index (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 68 publications
1
9
0
1
Order By: Relevance
“…We have previously performed a meta-analysis in rodents showing that birth weight is significantly decreased in prenatally stressed animals. 22 At weaning, PS-offspring of both sexes showed increased body weight in comparison to unstressed controls, supporting recent findings indicating that prenatal environment may influence the likelihood of developing overweight and obesity. 49 Restraint stress would modify maternal behavior contributing to the long-term effects observed in offspring.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…We have previously performed a meta-analysis in rodents showing that birth weight is significantly decreased in prenatally stressed animals. 22 At weaning, PS-offspring of both sexes showed increased body weight in comparison to unstressed controls, supporting recent findings indicating that prenatal environment may influence the likelihood of developing overweight and obesity. 49 Restraint stress would modify maternal behavior contributing to the long-term effects observed in offspring.…”
Section: Discussionsupporting
confidence: 80%
“…A recent meta-analysis conducted by our group showed that, in humans, PS was associated with increased body mass index in exposed offspring. 22 It has been proposed that when the postnatal environment matches the prenatal one, adaptations of the phenotype of the offspring are beneficial; however, when both environments do not match, these adaptations may lead to the development of different pathologies. 23 In this regard, in a recent meta-analysis of rodent studies, we found that birth weight was decreased in offspring exposed to PS, but then in the absence of a challenging environment, catch-up growth is prevented.…”
Section: Introductionmentioning
confidence: 99%
“…actions, promoting depression, metabolic syndrome, type 2 diabetes, and heart disease (Mastorci et al, 2009;Anisman et al, 2018;Burgueño et al, 2020). By the same token, some behavioral coping strategies (e.g., avoidant coping) might be effective in the short term but could potentially undermine the adoption of strategies (e.g., obtaining help) that are needed to contend effectively with the stressor in the longer term.…”
Section: Resiliencementioning
confidence: 99%
“…Littleton et al (2010) meta-analysis evaluating the relationship between psychosocial stress in pregnancy and negative perinatal outcomes found that MS affects both neonatal weight and the risk for LBW (Littleton et al, 2010). MS during intrauterine life has also been shown to affect a range of long-term outcomes (Burgueño et al, 2019). A study has found evidence to suggest that exposure to stressful conditions during preconception and the prenatal period may increase the risk for developing Type 2 Diabetes Mellitus in childhood and young adulthood.…”
Section: Translational Potentialmentioning
confidence: 99%